Analisis Efektivitas Integrasi Feeder pada Sistem Bus Rapid Transit (BRT) Kota Medan Berbasis Analisis Spasial - Ratih Permata Hapriani; Subarto Subarto; Fauzi Fauzi (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to analyze the effectiveness of the integration of the Bus Rapid Transit (BRT) system with feeder transportation in improving the connectivity and accessibility of public transportation in Medan City. The research methods used include field surveys, interviews, and spatial analysis based on Geographic Information Systems (GIS) to map the transportation network and assess the scope of services. The analysis was carried out by comparing the existing conditions of the BRT (Corridors 2 and 3) and the results of the simulation after the integration of five feeder routes (A2, A3, A6, A7, and A8). The results show that the integration of feeder routes is able to increase service coverage from 57.84 km² to 128.84 km² (an increase of 122.8%), as well as expand the served area from 23 to 44 zones, with an increase in service ratio from 26% to 57%. In addition, the average distance to the bus stop decreased from 1.2 km to 0.6 km, and the route overlap was reduced by 40%. Spatially, areas with high accessibility (<500 m from bus stops) have increased significantly in city centers such as Merdeka Square and Petisah Market. This study concludes that the integration of BRT and feeder is an effective strategy to realize a sustainable, efficient, and inclusive transportation system in the city of Medan. The implementation of a rotating operating system is also recommended to optimize the fleet without the need for the addition of new vehicles.